Design And Analysis Of Integrated Optical Branching Waveguides - Yong, Yik Seng (2005)
The main results of waveguide theory are the number of guided modes for a given dielectric profile and both the effective index and the optical field for each mode. Our research work in this area has mainly focused on modeling and analyzing "arbitry" waveguide structures with new functionality and device miniaturization by using effective index method (IEM) and 2-dimensional finite-difference beam propagation method (FD-BPM)